Efficacy and safety of trabeculectomy versus peripheral iridectomy plus goniotomy in advanced primary angle-closure glaucoma: study protocol for a multicentre, non-inferiority, randomised controlled trial (the TVG study) - Keith Barton; Tin Aung; Ling Jin; Ping Lu; Xiulan Zhang; Robert N Weinreb; Yi Zhang; Li Tang; Guangxian Tang; Hengli Zhang; Aiguo Lv; Huiping Yuan; et al. (BMJ Open)
Introduction Primary angle-closure glaucoma (PACG) is a major subtype of glaucoma that accounts for most bilateral glaucoma-related blindness globally. Filtering surgery is a conventional strategy for PACG, yet it has a long learning curve and undesirable disastrous complications. Minimally invasive glaucoma surgery (MIGS) plays an increasing role in the management of glaucoma due to its safer and faster recovery profile; cataract surgery-based MIGS is the most commonly performed such procedure in PACG. However, for patients with a transparent lens or no indications for cataract extraction, incorporation of MIGS into PACG treatment has not yet been reported. Therefore, this multicentre, non-inferiority, randomised controlled clinical trial aims to compare the efficacy and safety of trabeculectomy versus peripheral iridectomy plus an ab interno goniotomy in advanced PACG with no or mild cataracts.Methods and analysis This non-inferiority, multicentre, randomised controlled trial will be conducted at seven ophthalmic departments and institutes across China. Eighty-eight patients with no or mild cataracts and advanced PACG will be enrolled and randomised to undergo trabeculectomy or peripheral iridectomy plus ab interno goniotomy. Enrolled patients will undergo comprehensive ophthalmic examinations before and after surgery. The primary outcome is intraocular pressure (IOP) at 12 months postoperatively. The secondary outcomes are cumulative success rate of surgery, surgery-related complications and number of IOP-lowering medications. Participants will be followed up for 36 months postoperatively.Ethics and dissemination The study protocol was approved by the ethical committees of the Zhongshan Ophthalmic Center, Sun Yat-sen University, China (ID: 2021KYPJ191) and of all subcentres. All participants will be required to provide written informed consent. The results will be published in peer-reviewed journals and disseminated in international academic meetings.Trial registration number NCT05163951.